Avascular necrosis (AVN) of the hip in patients operated in the Orthopaedic Arthroplasty Unit at Chris Hani Baragwanath Academic Hospital - Mwoyofiri, Jephta (University of the Witwatersrand, Johannesburg, 2023)
Background: Avascular necrosis (AVN) of the femoral head is a progressive structural damage of the head of the femur because of interruption of blood supply to the subchondral bone resulting in the collapse of the head of the femur and secondary arthritis. Moreover, this chronic debilitating disease of the hip causes an immense contribution to the need for total hip arthroplasty (THA) and is common in young persons between the third and fifth decades of life. The aim of the study was to describe the causes of osteonecrosis of the femoral head (ONFH) in patients operated at Chris Hani Baragwanath Academic Hospital (CHBAH) Arthroplasty unit from 2017 to 2022. Methods: A retrospective review of all patients operated between the above-mentioned period, was conducted through collecting the patients’ demographic data, risk factors and treatment given. Results: The study had 285 participants with AVN from a total of 838 patients who had hip surgery. There were 149 (52%) females and 136 (48%) males. The mean age was 51.7 years with a SD 11.4 years. Majority of the patients were in the age group: 50 ‒ 59 years. The main risk factor of AVN was human immunodeficiency virus (HIV) with 117 (41%) patients. Those on highly active anti-retroviral therapy (HAART) were 115 (98%) patients. The median cluster of differentiation 4 (CD4) count was 584 (IQR 470 ‒ 711) and the viral load was undetected in 29 of the 32 (91%) patients with recorded viral load results. Ficat/Arlet stage 4 had 199 (70%) patients and all our patients had total hip replacement. Conclusion: ONFH contributes significantly to the burden of total joint arthroplasty in young patients. As our study has shown, there are several risk factors such as HIV, alcohol use and steroids being among the commonest. Our study draws attention to the significant burden that HIV has on hip pathology. HIV was the commonest cause of AVN at our local health institution and may be in the Sub-Saharan region. However, in our study we could not isolate HAART as a cause of AVN due to inadequate patient records. Majority of patients usually present with advanced stages of ONFH requiring a femoral head sacrificing operation due to late referral and long waiting list before surgery.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine, to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Avascular necrosis; Arthroplasty; Ficat/Arlet classification; Association Research Circulation Osseous; Chris Hani Baragwanath Hospital; Alcohol; HIV; Lupus; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education